A human alpha-arrestin protein with a potential role in cargo protein trafficking within the endocytic system - Lake, David Jonathan (2013)
β-Arrestins are essential adaptors for G protein-coupled receptor (GPCR) trafficking. Evolutionary ancestors of the β-arrestins – dubbed α-arrestins – are present in yeast/fungi and, similar to β-arrestins, recognise cargo proteins and mediate their intracellular trafficking. Mammalian α-arrestins include five largely uncharacterised arrestin domain-containing (ARRDC1-5) proteins that display a predicted arrestin structure; the current study focuses on human ARRDC2. Confocal microscopy of exogenous, fluorescent protein-tagged ARRDC2 in U2OS cells in combination with compartment-specific markers indicated that ARRDC2 is dynamically distributed throughout the plasma membrane and endocytic system, predominantly to late endosomes/lysosomes. Anti-ARRDC2 immunostaining in several primary cell lines broadly supported this conclusion. ARRDC2 contains two proline-rich (PPxY) motifs that in other α-arrestins have been reported to mediate interactions with WW domain-containing NEDD4 family E3 ubiquitin ligases. Coimmunoprecipitation indicated that ARRDC2 is able to interact with several NEDD4 E3s via its PPxY motifs, and confocal microscopy suggested that this interaction may influence the subcellular targeting of the ligases. Ubiquitination of ARRDC2 was detected by coimmunoprecipitation, although this modification was independent of ARRDC2 interaction with NEDD4 E3s. ARRDC2 colocalised with agonist-stimulated, internalised GPCRs (β2-adrenergic receptor (β2AR) and δ-opioid receptor (δOR)) and colocalisation analysis indicated that this involved compartmental redistribution of ARRDC2 to receptor-containing early/recycling endosomes, suggesting a specific effect. Interaction of ARRDC2 with δOR was detected using coimmunoprecipitation, and confocal analysis suggested that ARRDC2 may influence δOR and β2AR intracellular trafficking. ARRDC2 was also found to oligomerise with itself and the β-arrestins. Confocal microscopy showed that ARRDC2 overexpression can induce the redistribution of β-arrestin1 to ARRDC2-positive vesicles, and a punctate bimolecular fluorescence complementation (BiFC) signal was detected between ARRDC2 and β-arrestin2. From this, it is speculated that α-/β-arrestins may function cooperatively or competitively to mediate discrete GPCR sorting events in the endocytic pathway.